BMC Zoology – a home for all zoological research in the BMC series. Issue 1 (December 2016) - Krüger, Dirk; Packer, Laurence; Flatt, Thomas; Hoi, Herbert; Morand, Serge; Lieb, Bernhard; Malabarba, Luiz; Fenton, M.
Abstract This editorial accompanies the launch ofBMC Zoology, a new open access, peer-reviewed journal within theBMC series that considers manuscripts on all aspects of zoology.BMC Zoology will increase and disseminate zoological knowledge through the publication of original research, methodology, database, software and debate articles. With the launch ofBMC Zoology, theBMC series closes a gap in its portfolio of subject-specific research journals and is now able to cover all aspects of animal research together withBMC Ecology, BMC Evolutionary Biology andBMC Veterinary Research .